Synthesis, characterization and biological activities of three indole Schiff bases and their copper and nickel complexes / Nazzatush Shimar Jamaludin - Jamaludin, Nazzatush Shimar (2010)
Three derivatives of indole-3-carboxaldehyde with indole-3-acetic hydrazide and their copper(II) and nickel(II) complexes were synthesized. The Schiff base compounds were varied on the substituent where each compound holds a hydrogen, chlorine and bromine atom on the 5th position of indole-3-carboxaldehyde. The structures of the ligands and their complexes were elucidated by various characterization methods. All compounds were screened for their biological effects on neuroprotective screening (in vitro), acute toxicity test (in vivo), ethanol-induced gastric ulcer (anti-ulcer) and glucose tolerance test (antidiabetic). All compounds except bromine-containing compounds were not dose dependent while compounds with bromine displayed significant results, acting as inhibitory agents for ulcers at high dose (50mg/kg). They also revealed their potential effect in lowering blood glucose level at all doses tested. No abnormalities or mortality were found in mice within 24 hours but the cytotoxic effect on neuron NG108-15 cells was discovered when the cells were pretreated with 50μg/ml of the compounds prepared.